Bandit heaven : the Hole-in-the-Wall gangs and the final chapter of the Wild West - Clavin, Tom, 1954- (St. Martin's Press, 2024)
"From multiple New York Times bestselling author Tom Clavin comes the thrilling true story of the most infamous hangout for bandits, thieves and murderers of all time-and the lawmen tasked with rooting them out. Robbers Roost, Brown's Hole, and Hole in the Wall were three hideouts that collectively were known to outlaws as "Bandit Heaven." During the 1880s and '90s these remote locations in Wyoming and Utah harbored hundreds of train and bank robbers, horse and cattle thieves, the occasional killer, and anyone else with a price on his head. Clavin's Bandit Heaven is the entertaining story of these tumultuous times and the colorful characters who rode the Outlaw Trail through the frigid mountain passes and throat-parching deserts that connected the three hideouts-well-guarded enclaves no sensible lawman would enter. There are the "star" residents like gregarious Butch Cassidy and his mostly silent sidekick the Sundance Kid, and an array of fascinating supporting players like the cold-blooded Kid Curry, the gang leader, and "Black Jack" Ketchum (who had the dubious distinction of being decapitated during a hanging), among others. Most of the hard-riding action takes place in the mid- to late-1890s when Bandit Heaven came to be one of the few safe places left as the law closed in on the dwindling number of active outlaws. Most were dead by the beginning of the 20th century, gunned down by a galvanized law-enforcement system seeking rewards and glory. Ultimately, only Cassidy and Sundance escaped . . . to meet their fate 6000 miles away, becoming legends when they died in a fusillade of lead. Bandit Heaven is a thrilling read, filled with action, indelible characters, and some poignance for the true end of the Wild West outlaw"--